¿Cómo aportar al desarrollo sostenible haciendo un buen uso y aprovechamiento de subproductos como el bagazo de las micro cervecerías en Bogotá D.C.? (2022)
In the present work, an environmental problem generated by the increase in population is highlighted, which is directly related to a greater production of large industries and their current model of taking, making and discarding. What is sought is to propose a sustainable development alternative from a sector or a particular industry that is growing, such as the microbrewery, specifically in the city of Bogotá D.C., and through the use of a by-product from the brewing process, such as bagasse, we can opt for a take, make and recycle model, generating new products that can be implemented in the market, using waste as raw material, and thus reduce the amount of waste, in this case solids, whose final destination is sanitary landfills.